Board Reforms and Dividend Policy: International Evidence - Bae, Kee-Hong; El Ghoul, Sadok; Guedhami, Omrane; Zheng, Xiaolan (Journal of Financial and Quantitative Analysis, 2021)
Abstract We study the impact of board reforms implemented in 40 countries worldwide on corporate dividend policy. Using a difference-in-differences analysis, we find that firms pay higher dividends following the reforms. The increase in dividend payouts is more pronounced for firms with weak board governance in the pre-reform period and those in countries with strong external governance mechanisms. Our findings corroborate the dividend outcome model, which postulates that board reforms strengthen the monitoring role of the board and empower outside shareholders to force management to disgorge dividends.